The conversion method of reference parameters for systems analysis and information security risk assessment - Корченко, Олександр Григорович; Казмірчук, Світлана Володимирівна; Гололобов, Андрій Юрійович (Ukrainian Information Security Research Journal, 2013)
To implement the process of analysis and information risk assessment based on the expert judgments it is required to use some methods and means that make possible to handle with fuzzy input data, for example, presented in the linguistic form. There is a system where an assessment is based on the parametric trapezoidal fuzzy numbers. A practical implementation of this system requires an application of other types of fuzzy numbers. The development of capabilities of such system can be achieved through additional use of another type of parametric fuzzy numbers-triangular. To solve the task this paper suggests the conversion method of reference parameters, which provides an analytic function what enables to transform (the equivalent conversion) the terms of linguistic variables. Such a decision would make it possible to improve flexibility of developed means of analysis and information security risk assessment, which are based on the linguistic approach and use to describe the linguistic variables the triangular fuzzy numbers.